Narratives of Stress in Health Meanings of African Americans in Lake County, Indiana. Issue 10 (3rd October 2017) - Dutta, Mohan; Sastry, Shaunak; Dillard, Sydney; Kumar, Rati; Anaele, Agaptus; Collins, William; Roberson, Calvin; Dutta, Uttaran; Jones, Christina; Gillespie, Tony; Spinetta, Christine
ABSTRACT: Across the life course, African Americans bear an unequal burden of disease compared to other racial groups. In spite of the widespread acknowledgment of racial health disparities, the voices of African Americans, their articulations of health and their local etiologies of health disparities are limited. In this article, we highlight the important role of communication scholarship to understand the everyday enactment of health disparities. Drawing upon the culture-centered approach (CCA) to co-construct narratives of health with African Americans residents of Lake County, Indiana, we explore the presence of stress in the everyday narratives of health. These narratives voice the social and structural sources of stress, and articulate resistive coping strategies embedded in relationship to structures.